Kinetic resolution of indolines by asymmetric hydroxylamine formation - Wang, Gang (Nat Commun, 2021)
Catalytic kinetic resolution of amines represents a longstanding challenge in chemical synthesis. Here, we described a kinetic resolution of secondary amines through oxygenation to produce enantiopure hydroxylamines involving N–O bond formation. The economic and practical titanium-catalyzed asymmetric oxygenation with environmentally benign hydrogen peroxide as oxidant is applicable to a range of racemic indolines with multiple stereocenters and diverse substituent patterns in high efficiency with efficient chemoselectivity and enantio-discrimination. Late-stage asymmetric oxygenation of bioactive molecules that are otherwise difficult to synthesize was also explored.